Investigation on the effect of recasting palladium-silver alloy by argon arc vacuum pressure casting process - Pei-Ling Lai; Chin-Tzu Yeh; Po-Sung Fu; Jen-Hao Chen; Ting-Hsun Lan; Jen-Chyan Wang; Wen-Cheng Chen; Chun-Cheng Hung (Elsevier, 2023)
Background/purpose: Palladium-silver (Pd-Ag) alloys are important as an alternative to gold-based alloys. The purpose of this study was to investigate the effect of an argon-arc vacuum pressure casting process on the recasting of the Pd-Ag alloy. Materials and methods: The recasting Pd-Ag alloys were compared with conventional horizontal centrifugal (HC) casting to an argon (Ar)-arc vacuum pressure (Ar-arc/VP) casting. The first-generation castings were made from a Pd-Ag alloy purchased from a supplier. Next-generation castings were made from 50 wt% Pd-Ag alloy before casting and 50 wt% from previous castings. This sequence was repeated over three generations to form the 2nd, 3rd and 4th recasting ingots. The ingots were then measured for marginal accuracy, interfacial oxidation, hardness and phase identification. Results: The recasting success rate of recastibility reached 100%. Compared with the HC group, the Ar-arc/VP group had better edge precision, smaller oxide layer thickness and lower hardness. The comparison of X-ray diffraction intensity showed that the relative intensities of Pd and Ag in the first, second and third generations recasting of the Ar-arc/VP group were significantly higher than those of the HC group. Phase analysis showed that the trace elements of indium and tin contents in the Pd-Ag recasting ingots of the Ar-arc/VP group were higher than those of the HC group. Conclusion: The results showed that the casting process used for recasting affected the quality of the Pd-Ag alloy. Therefore, Ar-arc/VP casting process could improve the effect of Pd-Ag recasting and maintain the alloy properties in comparison with HC casting.